Optimalisasi Potensi Ekonomi Melalui Program Budidaya Lele Berbasis Syariah di Desa Kasang Kota Karang - Ridhwan Ridhwan; Sherly Bintani Awaliyah; Septianingsi; Nur Ngafiah; Tiara Fitri Melati (Lembaga Citra Pustaka, 2023)
Desa Kasang Kota Karang is one of the rural areas rich in agricultural and fish farming potential. One sector with great potential for development in this village is catfish farming. However, unfortunately, in recent years, the conditions and issues faced by catfish farming partners in this village have become a serious concern. One of the main problems is the neglect of existing catfish farming ponds in Desa Kasang Kota Karang, which have excellent potential for catfish cultivation. Therefore, Community Service activities through the Village Innovation Program (Pro-IDe) in Kasang Kota Karang are needed to optimize the Sharia-based catfish farming program. The stages of the Community Service Program conducted for catfish farming include the first stage of preparation, the second stage of socialization, the third stage of training, and the final stage of monitoring and evaluation. The socialization material covers the objectives and procedures for proper catfish cultivation. The results obtained from this activity aim to enable the community in Desa Kasang Kota Karang to establish good cooperation and enhance their ability to manage catfish farming properly. This, in turn, is expected to become an economic source and a flagship product for the community in Desa Kasang Kota Karang.